Open-label Study with Nalmefene as Needed Use in Alcohol-Dependent Patients with Evidence of Elevated Liver Stiffness and/or Hepatic Steatosis. (12th November 2019) - Mueller, Sebastian; Luderer, Mathias; Zhang, Doris; Meulien, Didier; Brach, Björn Steiniger; Schou, Maiken Brix
Abstract: Aims: This open-label study in patients with alcohol dependence and evidence of elevated liver stiffness and/or hepatic steatosis was designed to explore the efficacy of nalmefene (18 mg) in reducing alcohol consumption and its subsequent effects on a variety of clinically relevant liver parameters. Methods: Adult patients with a diagnosis of alcohol dependence and evidence of elevated liver stiffness and/or hepatic steatosis (liver stiffness >6 kPa or controlled attenuation parameter (CAP) >215 dB/m as measured by transient elastography) were recruited at two study sites in Germany. During the 12-week treatment period, patients were instructed to take nalmefene each day they perceived a risk of drinking alcohol. Results: All 45 enrolled patients took at least one dose of nalmefene and 39 completed the study. After 12 weeks of study treatment with nalmefene patients showed a reduction in alcohol consumption of −13.5 days/month heavy drinking days and −45.8 g/day total alcohol consumption. Most liver parameters showed modest changes at Week 12; there was a 13% decrease in liver stiffness and 10% reduction in CAP values. Results indicated non-significant negative associations between alcohol consumption and liver stiffness and/or CAP over this 12-week study. Nalmefene was generally well tolerated, and most adverse events were mild or moderate, the most frequent being dizziness. Conclusions: Patients treated with nalmefene for 12 weeks had reductions in alcohol consumption by 50% relative to baseline and showed trends to improvement in liver stiffness and CAP.